2019
DOI: 10.5937/leksir1939060d
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of antioxidant, antineurodegenerative and antidiabetic activities of Ocimum basilicum L., Laurus nobilis L. leaves and Citrus reticulata Blanco peel extracts

Abstract: Ocimum basilicum (sweet basil) and Laurus nobilis (bay leaves or laurel) have been used in traditional medicine for centuries, and also extensively employed as spices for adding aroma and flavor to various food products. Citrus reticulata (mandarin) is mainly used in food industry for juice production, while its peel as main byproduct contains high concentration of valuable substances. The samples were collected in Lastva Grbaljska (Montenegrin coast) and purchased from the market. Since the oxidative stress r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
(55 reference statements)
2
6
0
Order By: Relevance
“…Previously [ 23 ], our research group reported PACs (A- and B-types) and flavonol glycosides as the main components of Apollonias barbujana , Laurus novocanariensis (laurel), Ocotea foetens and Persea indica ( Figure 2 ), the most relevant Lauraceae species of Laurissilva. The anti-diabetic effects of similar plants ( Laurus nobilis , Persea americana and Ocotea bullata ) have been documented before [ 3 , 5 , 13 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], and similar properties were expected for targeted Lauraceae species. Therefore, this study was designed to evaluate for the first time the in vitro inhibitory effects of four Lauraceae plant extracts ( A. barbujana , L. novocanariensis , O. foetens and P. indica ) on digestive enzymes linked to the carbohydrates (α-amylase, and α-glucosidase) and lipids metabolism (pancreatic lipase), aldose reductase and protein glycation.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Previously [ 23 ], our research group reported PACs (A- and B-types) and flavonol glycosides as the main components of Apollonias barbujana , Laurus novocanariensis (laurel), Ocotea foetens and Persea indica ( Figure 2 ), the most relevant Lauraceae species of Laurissilva. The anti-diabetic effects of similar plants ( Laurus nobilis , Persea americana and Ocotea bullata ) have been documented before [ 3 , 5 , 13 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], and similar properties were expected for targeted Lauraceae species. Therefore, this study was designed to evaluate for the first time the in vitro inhibitory effects of four Lauraceae plant extracts ( A. barbujana , L. novocanariensis , O. foetens and P. indica ) on digestive enzymes linked to the carbohydrates (α-amylase, and α-glucosidase) and lipids metabolism (pancreatic lipase), aldose reductase and protein glycation.…”
Section: Introductionsupporting
confidence: 68%
“…Ocotea bullata bark extracts demonstrated high inhibition of carbohydrate-metabolizing enzymes [ 24 ]. Different extracts of L. nobilis (bay laurel) inhibited α-glucosidase metabolic activity [ 3 , 13 ]. L. nobilis effectively inhibited α-amylase, but Cinnamomum verum (true cinnamon) extract was much more effective [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of the potential neuroprotective activity of various leaf extracts was performed in a study by Duletić-Laušević et al [ 47 ]. The highest AChE inhibition (%) was obtained by the water extract of commercial L. nobilis (90.72%), followed by acetonic and methanolic extracts.…”
Section: Laurus Nobilis (Lauraceae)mentioning
confidence: 99%
“…The highest AChE inhibition (%) was obtained by the water extract of commercial L. nobilis (90.72%), followed by acetonic and methanolic extracts. Since the acetone extract of L. nobilis showed the highest antioxidant activity (total phenolic content, TPC) and α-glucosidase inhibition, while the water extract of commercial bay laurel exhibited the highest AChE inhibition, the bay leaves could be a promising antioxidant, neuroprotective, and antidiabetic agent [ 47 ].…”
Section: Laurus Nobilis (Lauraceae)mentioning
confidence: 99%